Needs and emotions creating strong customer’s motivation in tourism - Lukianets, Halyna (My University, 2022)
Choice of where and how to travel is often taken by a traveler based on two decision-making strategies, bottom-up, i.e. needs-driven, or top-down, i.e. emotion-driven, which will be explained in detail herein. The topicality of this study is determined by the necessity to identify the motives, which effect tourist’s decision-making process on where to go, what to do, how to travel and where to stay.
Keywords: needs and emotions; customer’s motivation; tourism industry; потреби та емоції; мотивація клієнта; індустрія туризму; кафедра іноземних мов професійного спрямування